Predictive Pseudo-Steady-State Mechanistic Model for Chain Reactions in Petrochemical Furnace Reactors - Ajor, Wordu Animia (International Journal of Chemical and Process Engineering Research, 2020)
The research predicts the application of pseudo steady-state mechanism to chain reactions. Process chain reactions taking place in a petrochemical furnace reactor generates many intermediates species, and the material balance process are written in the kinetic balance to account for the contributory effects of the intermediates species than assuming negligible concentrations in the kinetic balance process. A set of material balance model on the number of molecules cum intermediates species resulting from the free radicals’ mechanism of the initiation, propagation, and termination all taking place in the furnace reactor were developed; and resolved simultaneously with energy/temperature balance of the radiative-convective zones of the petrochemical furnace reactor. A mat-lab simulation process applying the petrochemical plant process data as boundary conditions, gave plot profiles of the molecules (ethylene, hydrogen, methane, and butane) and active intermediates of (methyl, ethyl, and hydrogen) and a clear flat plateau which mainly depicts applicability of pseudo steady-state mechanism in kinetic studies. The models predict the following results ethane cracking 5.57%. ethylene formation 14.6%, temperature effects 0.03% and pressure drop 3.5 % which is very adequate for the petrochemical furnace reactor operations industrially. Finally, the essence of the work is to demonstrate how intermediates species formed in reactions process should be incorporated in any given material balance model to account for the overall kinetic studies rather than neglecting as zero contributions in any process chemistry.